Patterns of use of systemic therapies among patients with metastatic melanoma: a retrospective claims database analysis in the United States. (18th August 2017) - Ma, Qiufei; Chen, Yaozhu Juliette; Hines, Dionne M.; Munakata, Julie; Batty, Nicolas; Barber, Beth Louise; Zhao, Zhongyun
Abstract: Objectives: This retrospective analysis of the IMS PharMetrics Plus claims database aimed to describe the current real-world treatment patterns for metastatic melanoma in the USA. Methods: Included patients (aged ≥18 years) had ≥1 prescription for ipilimumab, vemurafenib, temozolomide or dacarbazine between 1 January 2011 and 31 August 2013; diagnosis of melanoma and metastasis before first use (index date); no index drug use prior to the index date; continuous health plan enrollment for ≥6 months before and ≥3 months after index date. Proportion of days covered (PDC) was defined as days exposed to index therapy divided by continuously enrolled days between index date and last prescription date. Results: Overall, 1043 patients were included (median age 57 years, 63% male), of whom 39% received the index drug ipilimumab, 35% vemurafenib, 19% temozolomide and 7% dacarbazine. Mean treatment duration (days) was 174 (vemurafenib), 100 (temozolomide) and 64 (dacarbazine). Mean PDC was 81% (vemurafenib), 67% (temozolomide) and 51% (dacarbazine). For patients receiving ipilimumab, 58% had the full 4 doses, 20% 3 doses, 14% 2 doses and 9% 1 dose only for the first induction course; 4% received re-induction, and none had a second re-induction. Conclusions: This study provides insights into the treatment patterns for metastatic melanoma, including newer agents, in real-world clinical practice.